Regional inequalities in residential energy use of Hungarian urban areas - Zoltán Nagy; Tekla Sebestyén Szép; Dóra Szendi (Trends Economics and Management, 2019)
Purpose of the article: Cities account for 60-80% of global energy consumption, and based on projections the development of urban areas will be the main engine of energy use growth in the future. Understanding and analysing the urban energy use and clarifying social and spatial inequalities is essential to make conscious energy policy decisions and gather feedback. A clear road map is needed for implementation of policy on decentralized energy. Methodology/methods: The analysis covers 23 Hungarian towns with county rights and Budapest during the period of 2010-2015. Simple statistical indices are calculated: the range ratio, range, relative range, dual index, standard deviation, relative standard deviation, absolute average difference. Scientific aim: The spatial distribution of energy use may contribute not only to understanding the decentralization process of energy systems but to forming a new energy policy that moves towards regional level and is highly decentralized. In this study, our main objective is to examine the Hungarian residential energy use revealing the regional disparities of urban energy use. Findings: In the case of the examined cities, significant inequalities and large spatial variances were not revealed with regard to the indicators of urban energy consumption (i.e. residential electricity consumption per household, residential gas consumption per household). However, the already small territorial differences typically decreased between 2010 and 2015. Conclusions: We conclude that significant differences regarding urban (23 Hungarian towns with county rights and Budapest) energy use were not experienced.
Keywords: R10; R11; Q49; 650; residential energy use; disparities; Hungary; dual index; electricity; natural gas